PANDANGAN HUKUM ISLAM TERHADAP JUAL BELI PAKAIAN BEKAS (THRIFT) DI PURWOKERTO - Azzahra, Bunga Abiyya; Isti'anah, Isti'anah (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
Thrifting growing popularity in Indonesia because it provides an opportunity for buyers to get clothes at affordable prices and can help reduce textile waste. Thrifting is great demand by people of all ages. Therefore, this research aims to find out how the practice of buying and selling used clothes (thrift) and how Islamic law views the buying and selling of used clothes (thrift) in Purwokerto City. Type of research methodology that used is field research in which researchers conduct direct research on thrift store in Purwokerto, such as Kayanaku.idn and Lucianz Sneakers. The data source used is primary data consisting of important information such as written notes from observations, interviews, and documentation obtained directly from respondents, and secondary data that is additional obtained from books, internet, research reports and scientific journals that have relevance with this research. The final results of this research are that the sale and purchase of used clothing (thrift) in Purwokerto is allowed according to Islamic law as long as it is carried out in accordance with the principles and conditions has been fixed.